2003
DOI: 10.1093/chemse/28.5.397
|View full text |Cite
|
Sign up to set email alerts
|

Taste Perception with Age: Generic or Specific Losses in Supra-threshold Intensities of Five Taste Qualities?

Abstract: The influence of ageing on supra-threshold intensity perception of NaCl, KCl, sucrose, aspartame, acetic acid, citric acid, caffeine, quinine HCl, monosodium glutamate (MSG) and inosine 5'-monophosphate (IMP) dissolved in water and in 'regular' product was studied in 21 young (19-33 years) and 21 elderly (60-75 years) persons. While the relative perception (intensity discrimination) seems to be remarkably resistant to the effect of ageing, the absolute perception (intensity rating) decreased with age for all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
148
3
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(170 citation statements)
references
References 40 publications
13
148
3
6
Order By: Relevance
“…Generally, gustatory and olfactory abilities decreased with increasing age and were higher in females than in males. These findings are in line with earlier studies (Schiffman and Warwick, 1993;Doty, 1994;Koskinen et al, 2003a, b;Mojet et al, Figure 3 Perception of sweet, sour, bitter and salty taste according to BMI and reporting of body weight in o65 years (n ¼ 210) and X65 years (n ¼ 101) subjects. Differences in taste perception could be observed for sour and bitter taste, whereas no significant differences for BMI and reporting of body weight were found for sweet and salty taste.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, gustatory and olfactory abilities decreased with increasing age and were higher in females than in males. These findings are in line with earlier studies (Schiffman and Warwick, 1993;Doty, 1994;Koskinen et al, 2003a, b;Mojet et al, Figure 3 Perception of sweet, sour, bitter and salty taste according to BMI and reporting of body weight in o65 years (n ¼ 210) and X65 years (n ¼ 101) subjects. Differences in taste perception could be observed for sour and bitter taste, whereas no significant differences for BMI and reporting of body weight were found for sweet and salty taste.…”
Section: Discussionsupporting
confidence: 91%
“…One method for treatment involves a sensory enhancement of foods with flavors and MSG. Several studies showed that amplification of flavor and taste can improve food palatability, increase salivary flow and local immunity and thereby at least acceptance of food (Schiffman, 2000;Mojet et al, 2003).…”
Section: Physiology Of Glutamatementioning
confidence: 99%
“…There is evidence that ability to detect taste varies with age (Hyde and Feller 1981; Chauhan and Hawrysh 1988; Mojet et al. 2001, 2003; Fukunaga et al. 2005; Heft and Robinson 2010; Imoscopi et al.…”
Section: Discussionmentioning
confidence: 99%
“…2012), gender (Hyde and Feller 1981; Chauhan and Hawrysh 1988; Mojet et al. 2001, 2003; Heft and Robinson 2010), and genetic variation in taste sensitivity to 6‐n‐propylthiouracil (PROP) (Bartoshuk et al 1994; Bartoshuk 2000; Tepper et al. 2009; Hayes and Keast 2011; Steele et al.…”
Section: Discussionmentioning
confidence: 99%